2016
DOI: 10.3791/53843
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput CRISPR Vector Construction and Characterization of DNA Modifications by Generation of Tomato Hairy Roots

Abstract: Targeted DNA mutations generated by vectors with clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 technology have proven useful for functional genomics studies. While most cloning strategies are simple to perform, they generally use multiple steps and can require several days to generate the ultimate constructs. The method presented here is based on DNA assembly and can produce fully functional CRISPR vectors in a single cloning reaction. Vector construction can also be pooled, further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Due to genetic redundancy for MYBA5/6/7 and TAS4a/b/c loci, it remains to be determined whether the events characterized here will have visible phenotypes impacting anthocyanin pigmentation and/or PD resistance/tolerance. Future experiments can employ multiple guide constructs (Jacobs and Martin 2016) to target all MYBA and TAS4 family members, and to target the sole Vvi-MIR828 locus at locations upstream or downstream of the mature miR828 in the hairpin structure to generate leaky dominant-negative alleles predicted to alter DICER processing efficiency. Our initial test construct for Vvi-MIR828 aimed to create null alleles by targeting the mature miR828 duplex per se but we failed to recover any regenerants, consistent with a speculated essential function of MIR828.…”
Section: Discussionmentioning
confidence: 99%
“…Due to genetic redundancy for MYBA5/6/7 and TAS4a/b/c loci, it remains to be determined whether the events characterized here will have visible phenotypes impacting anthocyanin pigmentation and/or PD resistance/tolerance. Future experiments can employ multiple guide constructs (Jacobs and Martin 2016) to target all MYBA and TAS4 family members, and to target the sole Vvi-MIR828 locus at locations upstream or downstream of the mature miR828 in the hairpin structure to generate leaky dominant-negative alleles predicted to alter DICER processing efficiency. Our initial test construct for Vvi-MIR828 aimed to create null alleles by targeting the mature miR828 duplex per se but we failed to recover any regenerants, consistent with a speculated essential function of MIR828.…”
Section: Discussionmentioning
confidence: 99%
“…Three gRNAs were selected to specifically target each of the LRR-XII gene family members as well as a control phytoene desaturase (PDS), as a knockout would result in obvious photobleaching (Liu et al, 2002; Supplemental Table S1). The 165 gRNAs were synthesized, pooled, and cloned into a Cas9 binary vector using DNA assembly (Jacobs and Martin, 2016). Sequencing of 105 Escherichia coli clones indicated that there was no obvious gRNA bias from the library preparation (Supplemental Table S2).…”
Section: Targeting the Lrr-rlk Subfamily XII Gene Family In Tomatomentioning
confidence: 99%
“…For each gene, the target sequences and their coordinates were extracted, and a custom Perl script was used to select the top three nonoverlapping gRNAs for each gene. Oligonucleotides were designed with the GN 19 sequences plus 20-nucleotide overlapping regions of the MtU6 promoter and scaffold for DNA assembly with NEBuilder HiFi DNA Assembly Master Mix (New England Biolabs), as described previously (Jacobs and Martin, 2016). Oligonucleotides were synthesized and pooled in equimolar amounts by Integrated DNA Technologies.…”
Section: Designing Grna Targets and Library Cloningmentioning
confidence: 99%
“…Overexpressing transgenic lines were generated with EVE under control of the 35S cauliflower promoter. For generation of CRISPR/Cas9 EVE mutant plants, a guide RNA (gRNA) targeting EVE was selected from http://aspendb.uga.edu/ (56), and cloned as previously described (57). Constructs were transferred into Agrobacterium and transformation of the hybrid (P. tremula × alba) poplar genotype 717-1B4 was performed (58).…”
Section: Methodsmentioning
confidence: 99%